The Invisible Hands of Political Parties in Presidential Elections: Party Activists and Political Aggregation from 2004 to 2012 - Dowdle, A. author. aut Link
XII, 143 p. 3 illus.
Keywords: This book looks at networks of individual donors during early stages of presidential primary electons to determine party unity. It directly challenges the commonly-held perception that a "divisive" primary is a problem for the political party in the general election.